2017
DOI: 10.5330/1096-2409-21.1.130
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors' Roles in RAMP and PBIS a Phenomenological Investigation (Part Two)

Abstract: Researchers conducted a qualitative, phenomenological investigation of the lived experiences of a sample of 10 school counselors in current or recent RAMP (Recognized ASCA [American School Counselor Association] Model Program) schools that also implemented positive behavioral interventions and supports (PBIS) with high fidelity. Researchers found two themes and related subthemes regarding school counselor roles. The first theme was school counselors' roles and responsibilities, with subthemes (a) makes sense w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Furthermore, the competencies identified in both the teaching and school counseling literature regarding classroom management were generally reflected in the results presented here, such as building positive relationships with students (Blake, 2017; Buchanan et al, 2017; Kwok, 2017; Skiba et al, 2016), use of both specific classroom management techniques and school-wide systems of evidence-based classroom management practices like positive behavioral interventions and supports (Ficarra & Quinn, 2014; Goodman-Scott & Grothaus, 2017; Moore et al, 2017; Quarto, 2007; Sanetti et al, 2018), the need for engaging and relevant lessons (Buchanan et al, 2017; Skiba et al, 2016), and sharing specific feedback with students while also seeking their responses (Blake, 2017; Geltner et al, 2011; Mitchell et al, 2017). Also, with the documented biases that teachers and school counselors harbor (Cole & Grothaus, 2014; Endo, 2017; Geltner et al, 2011), the call for culturally competent classroom management was endorsed by this study.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the competencies identified in both the teaching and school counseling literature regarding classroom management were generally reflected in the results presented here, such as building positive relationships with students (Blake, 2017; Buchanan et al, 2017; Kwok, 2017; Skiba et al, 2016), use of both specific classroom management techniques and school-wide systems of evidence-based classroom management practices like positive behavioral interventions and supports (Ficarra & Quinn, 2014; Goodman-Scott & Grothaus, 2017; Moore et al, 2017; Quarto, 2007; Sanetti et al, 2018), the need for engaging and relevant lessons (Buchanan et al, 2017; Skiba et al, 2016), and sharing specific feedback with students while also seeking their responses (Blake, 2017; Geltner et al, 2011; Mitchell et al, 2017). Also, with the documented biases that teachers and school counselors harbor (Cole & Grothaus, 2014; Endo, 2017; Geltner et al, 2011), the call for culturally competent classroom management was endorsed by this study.…”
Section: Discussionmentioning
confidence: 60%
“…Similar to studies of comprehensive school counseling programs generally, the majority of these studies have been quantitative in design. In fact, only two published articles (Goodman-Scott & Grothaus, 2017a, 2017b) investigated RAMP qualitatively.…”
Section: Why Does It Matter?mentioning
confidence: 99%
“…Others have shown that RAMP school counselors score higher on social justice advocacy measures than school counselors in schools without RAMP (Feldwisch & Whiston, 2016) and have a thorough understanding of the importance of using data in planning and implementing student services (Young & Kaffenberger, 2011). Goodman-Scott and Grothaus (2017a, 2017b) examined the extent to which school counselors across elementary and secondary schools saw positive behavioral interventions and supports (PBIS) and RAMP as mutually beneficial to one another and found that school counselors saw coordinating PBIS efforts as an important role for school counselors.…”
Section: Why Does It Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the breadth and depth of MTSS implementation across the country, a number of scholars have suggested that school counselors’ roles naturally align with the MTSS framework (Goodman‐Scott et al., 2016, 2019, 2020; Ockerman et al., 2012; Ziomek‐Daigle et al., 2016). These claims have been backed empirically, as a number of scholars have demonstrated school counselors’ role in MTSS (Betters‐Bubon & Donohue, 2016; Betters‐Bubon et al., 2016; Cressey et al., 2014; Goodman‐Scott, 2014; Goodman‐Scott & Grothaus, 2017a, 2017b). For instance, some studies found that school counselors may act as leaders in MTSS.…”
Section: School Counselingmentioning
confidence: 99%